Language, gender and feminism : theory, methodology and practice - Mills, Sara.; Mullany, Louise (Abingdon, Oxon ; New York : Routledge, 2011)
Language, Gender and Feminism presents key contemporary theoretical perspectives, methodologies and analytical frameworks in the field of feminist linguistic analysis. Mills and Mullany cover a wide range of contemporary feminist theories and emphasise the importance of an interdisciplinary approach. Topics covered include: power, language and sexuality, sexism and an exploration of the difference between second and third wave feminist analysis. Each chapter presents examples from research conducted in different cultural and linguistic contexts which allows students to observe practical applications of all current theories and approaches. Throughout oral and written language data, from a wealth of different contexts, settings and sources, is thoroughly analysed. The book concludes with a discussion of how the field could advance and a overview of the various research methods, pertinent for future work in language and gender study.
CHAPTER 1: Contemporary Issues in Language, Gender and Feminism CHAPTER 2: Why We Still Need Feminism CHAPTER 3: Theorising Gender CHAPTER 4: Feminist Linguistic Approaches CHAPTER 5 Methodological approaches CHAPTER 6: Sexuality CHAPTER 7: Sexism CHAPTER 8: Future Directions.
Julkaistu myös verkkoaineistona.
Keywords: Feminist theory; Language and languages -- Gender; Language and languages -- Sex differences; Sexism in language; Sociolinguistics; Women -- Language; feministinen tutkimus; kielenkäyttö; kieli ja kielet; naiset; seksismi; sosiolingvistiikka; sukupuoli; sukupuolierot; feministisk forskning; språkbruk; språk; kvinnor; sexism; sociolingvistik; kön; könsskillnader